Professional Identity Promoting Professional Development of Teachers in Forestry Science Based on Survival Analysis Model - Li Liqin (Forest Chemicals Review)
Survival analysis model is one of the common analysis models in forest industrial manufacturing. Based on the survival analysis model, this paper studies the role of professional identity in promoting professional development of teachers in forestry science. Teachers with different professional identity have different development characteristics in all aspects of professional structure. On the basis of field interviews, this study analyzes four ways that teachers’ professional identity affects their professional development. The results show that professional identity can stimulate the persistence of teachers’ professional beliefs and promote the reasonable construction of teachers’ professional ideas; Professional identity can stimulate teachers’ reflection and accumulation. Professional identity can promote the development of teachers’ professional knowledge and ability. Professional identity can stimulate the motivation of teachers’ development and affect the formation and change of professional attitude motivation. Professional identity can promote teachers’ awareness of self professional development and tend to the ideal state of professional development. The results of this study have a certain reference value for the research on the promotion of teachers’ professional identity to professional development.